Determinants of Internet skills, uses and outcomes. A systematic review of the second- and third-level digital divide. Issue 8 (December 2017) - Scheerder, Anique; van Deursen, Alexander; van Dijk, Jan
Highlights: This article presents a literature review on determinants of the digital divide. Consistent digital divide terminology is missing within the literature. The majority of determinants identified focuses on the second-level digital divide. Sociodemographic and socioeconomic determinants are studied the most. More attention should be devoted to the outcomes of Internet use. Abstract: Recently, several digital divide scholars suggested that a shift is needed from a focus on binary Internet access (first-level digital divide) and Internet skills and use (second-level digital divide) to a third-level digital divide in which the tangible outcomes of Internet use are highlighted. A plethora of studies have been conducted to identify determinants of digital divides. Unfortunately, there is a lack of consistency in the terminology used. Moreover, terms are often not theoretically grounded. Therefore, we conducted a systematic literature review of digital divide determinants. The results show that the third-level digital divide was underexposed. The primary focus is on Internet use. More importantly, the identified determinants show that digital divide research is largely limited to sociodemographic and socioeconomic determinants.